Dampak Penyapihan Menurut Al-Quran Dalam Meningkatkan Kematangan Psikologi Anak Masa Kini: Studi Terhadap QS. Al Baqarah ayat 233 Dalam Dunia Pendidikan - Baktiar Leu (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
This article aims to discuss the impact of weaning according to the Qur'an in increasing the psychological maturity of children. Weaning is inseparable from the discussion about breastfeeding. Therefore, this paper begins with a discussion of the definition of breastfeeding and weaning, the legal basis, types of weaning, weaning methods, the impact of weaning at the age of two and weaning and finally the psychological maturity of children. This paper is classified as library research, where the author uses a multidisciplinary approach, namely interpretive, legal, sociological, psychological approaches and books that have relevance to the problems discussed, then reviews and concludes. In general, in this paper the author describes that basically breastfeeding is seen as a mother's obligation to her child after giving birth. Allah SWT mentions it in QS Al-Baqarah verse 233. The command to breastfeed is conditional with benefits and benefits for both the baby and the mother, both physically and psychologically. The length of breastfeeding period based on QS Al-Baqarah verse 233 is for two years for those who want to perfect it. However, it may be less than two years if there is deliberation between the two parents with various considerations. Weaning is stopping a child from suckling its mother. Weaning in two years has a very positive impact on children's development both from the health and psychological aspects so that religion strongly recommends it